Cultures of the countryside : art, museum, heritage, and environment, 1970-2015 - Sekules, Veronica (London : Routledge, 2018)
"Cultures of the Countryside examines the relationship between the museum and the micro-cultures of the countryside. Offering an exploration of museums and heritage projects in the UK that have attempted to introduce new ways of engagement between localities, objects, and people, this book considers how museums, heritage initiatives, and art projects have dealt with pressing local and global socio-political issues relating to the environment and rural life, including changing demographics and rural practices, local environmental concerns, and global climate activism. Providing a thorough examination of the representation of competing histories, visions and politics, Sekules asks whether museums and heritage projects can engage actively in shaping cultures, as well as reflecting them. At the core of the analysis is an examination of the findings from a project in the UK's East Anglia, 'The Culture of the Countryside', from which emerged themes closely bound to different countryside landscapes, peoples and heritage. Aimed at practitioners and students alike, Cultures of the Countryside provides a unique insight into the roles of the museum and heritage projects in rural and environmental issues in the recent past, whilst also offering perspectives and recommendations for the future."--Provided by publisher.
Chapter 1 Countrification -- chapter 2 Nostalgia, art and folk life -- chapter 3 Heritagisation and the 'open air' -- chapter 4 Education and the countryside -- chapter 5 Global village -- chapter 6 At the edge of the farm -- chapter 7 The local contemporary -- chapter 8 Changing landscapes.
OCLC-licensed vendor bibliographic record.
Keywords: Ethnological museums and collections -- Great Britain; BUSINESS & ECONOMICS -- Museum Administration & Museology; REFERENCE -- General; TRAVEL -- Museums, Tours, Points of Interest; LANGUAGE ARTS & DISCIPLINES / Library & Information Science